Effects of temperature on wild chili pepper (Capsicum annuum var. glabriusculum) germination grown under two light conditions (2017)
The populations of wild chili pepper (Capsicum annuum var. glabriusculum) are a genetic valuable resource and the knowledge of the germinative ability, is of great importance for its management and conservation. The effects of the temperature on germination of wild chili grown in two environment of light, and the relation with the weight of 100 seeds of five populations of wild chili of the Northwest of Mexico, were recorded. The mother plants grown in greenhouse conditions with 50 and 100 % of solar light. The treatments applied in the germination cameras matched: Fluctuating temperature (25-35 ºC) and constant temperature (25 ºC). The treatment variables were the following: percentage of final germination and mean germination time (T50). These variables performed a greatest treatment response of fluctuating temperature. A widely variation among 50 and 100 % of light was recorded with natural conditions. These temperature fluctuations are determinant in germinative processes. The temperature performed a significantly response in terms of the effect in germination velocity (T50) but not in germination percentage. The final germination was not significantly correlated with the seed weight due to maternal effects. In addition, plants grown in greenhouse conditions, differentiate among populations with a genetic basis.